2023
DOI: 10.3390/nano13040668
|View full text |Cite
|
Sign up to set email alerts
|

Pd/Pt-Bimetallic-Nanoparticle-Doped In2O3 Hollow Microspheres for Rapid and Sensitive H2S Sensing at Low Temperature

Abstract: H2S is a poisonous gas that is widespread in nature and human activities. Its rapid and sensitive detection is essential to prevent it from damaging health. Herein, we report Pd- and Pt-bimetallic-nanoparticle-doped In2O3 hollow microspheres that are synthesized using solvothermal and in situ reduction methods for H2S detection. The structure of as-synthesized 1 at% Pd/Pt-In2O3 comprises porous hollow microspheres assembled from In2O3 nanosheets with Pd and Pt bimetallic nanoparticles loaded on its surface. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…[42][43][44] In addition, compared to single metal doping, bimetallic doping probably exhibits synergistic effects due to geometric effects, electronic interactions, and chemical reactions, which can simultaneously catalyze and sensitize the parent material, and thus improve the selectivity. For instance, K. Jiang et al 42 reported Pd/Pt bimetallic-NP-doped In 2 O 3 hollow microspheres that were synthesized using solvothermal and in situ reduction methods for H 2 S detection. It was found that 1 at% Pd/Pt In 2 O 3 composites exhibit strong selectivity and sensing performance (as shown in Fig.…”
Section: Sensors and Diagnostics Tutorial Reviewmentioning
confidence: 99%
“…[42][43][44] In addition, compared to single metal doping, bimetallic doping probably exhibits synergistic effects due to geometric effects, electronic interactions, and chemical reactions, which can simultaneously catalyze and sensitize the parent material, and thus improve the selectivity. For instance, K. Jiang et al 42 reported Pd/Pt bimetallic-NP-doped In 2 O 3 hollow microspheres that were synthesized using solvothermal and in situ reduction methods for H 2 S detection. It was found that 1 at% Pd/Pt In 2 O 3 composites exhibit strong selectivity and sensing performance (as shown in Fig.…”
Section: Sensors and Diagnostics Tutorial Reviewmentioning
confidence: 99%